A TURN-TAKING STRATEGY OF CONVERSATION ANALYSIS IN THE CLASSROOM - Rosi Rosanti; Euis Rina Mulyani (IKIP Siliwangi, 2023)
A conversation is an important form of communication that involves more than two people. Conversations are used to provide information, express ideas, opinions, or feelings, and many other things. The topic of the conversation is very relevant to everyday life. To obtain useful information, both parties should conduct the conversation properly. In conversation, they should understand each other's strategy. A successful conversation can be achieved by employing a turn-taking strategy, which is considered an essential component of a conversation. This study looked at turn-taking as a conversation strategy used by EFL students in grade VII at a junior high school in Cimahi. This research instrument used file notes and video recording to record classroom activities while teaching and learning process. This research used a descriptive qualitative method to identify and describes the phenomenon of the strategies and types of turn-taking. In this research, the researcher gained the following results: 1) Taking the floor it means is where the first speaker takes overturn to speak. it is consists of starting up, taking over, interruption, over-left. 2) Holding the floor means to carry to talk, and 3) Yielding the floor means giving a turn to the next speaker and the first speaker gives the response. Keywords: Conversation Analysis; Turn-taking Strategy